Multidomain Connectivity as a Marker of HIIT-Induced Adaptation in Elite Youth Soccer Players: A Correlational Mapping Approach - Moses Gnanasigamani; Agnieszka Kaczmarek; Jarosław Nosal; Eugenia Murawska-Ciałowicz; Paweł Chmura (Applied Sciences, 2025)
This study investigated the effects of high-intensity interval training (HIIT) in elite youth soccer players using a novel multidomain correlational mapping approach. A four-week HIIT intervention was applied in a randomized controlled design, with physiological, cognitive, and neuromuscular data collected through laboratory, field-based, and biochemical tests. Metrics such as VO2max, BDNF levels, lactate dynamics, and cognitive load were analyzed across time points and groups. HIIT elicited statistically significant improvements in aerobic capacity, buffering efficiency, and perceptual-cognitive function, with a notable emergence of cross-domain associations. Unlike the control group, HIIT participants showed strengthened correlations between metabolic, cognitive, and neuromuscular indices, such as lactate slope with exertion perception and BDNF response with cardiac recovery. Hierarchical clustering further revealed tightly integrated multidomain clusters in the HIIT group, absent in the controls, suggesting a reorganization of physiological networks. These findings support the concept that HIIT not only improves discrete capacities but fosters systemic adaptation through enhanced inter-domain coordination. These results align with emerging frameworks in network physiology and highlight the potential for using correlation structures as biomarkers of holistic training adaptation. This multidimensional perspective offers new insights into how targeted training reshapes performance-related systems and may inform individualized athletic programming.